2020
DOI: 10.1111/desc.13022
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Cerebellar Resting‐State Functional Connectivity Related to Reading Performance in Struggling Readers

Abstract: Reading is a critical neurodevelopmental skill for school‐aged children, which requires a distributed network of brain regions including the cerebellum. However, we do not know how functional connectivity between the cerebellum and other brain regions contributes to reading. Here we used resting‐state functional connectivity to understand the cerebellum's role in decoding, reading speed, and comprehension in a group of struggling readers (RD) and a group of adolescents and children with typical reading abiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 61 publications
(74 reference statements)
0
7
1
Order By: Relevance
“…It did, however, find more intrinsic functional connectivity between a seed region in right crus I and three left-hemisphere perisylvian target seed regions, angular gyrus, posterior superior temporal gyrus, and inferior frontal gyrus ( Ashburn et al, 2020 ). A more recent resting-state iFC study by Greeley et al (2021) found both weaker and stronger functional connectivity in a group of children with dyslexia (compared to a control group) between cerebellar right crus I, right lobule VI, and right lobule VIII seeds and widespread motor and non-motor regions of the cerebral cortex. Further, functional connections between right cerebellar lobule VIII and right frontal pole, and between cerebellar lobule VIII and left angular gyrus were positively related to reading measures in the group with dyslexia.…”
Section: Discussionmentioning
confidence: 94%
“…It did, however, find more intrinsic functional connectivity between a seed region in right crus I and three left-hemisphere perisylvian target seed regions, angular gyrus, posterior superior temporal gyrus, and inferior frontal gyrus ( Ashburn et al, 2020 ). A more recent resting-state iFC study by Greeley et al (2021) found both weaker and stronger functional connectivity in a group of children with dyslexia (compared to a control group) between cerebellar right crus I, right lobule VI, and right lobule VIII seeds and widespread motor and non-motor regions of the cerebral cortex. Further, functional connections between right cerebellar lobule VIII and right frontal pole, and between cerebellar lobule VIII and left angular gyrus were positively related to reading measures in the group with dyslexia.…”
Section: Discussionmentioning
confidence: 94%
“…A comparison of high- and low-fluency readers in English also showed reduced FC in low-fluency readers within two cognitive control networks: the cingulo-opercular (CO) and ventral attention (VA) networks (Freedman et al, 2020), the latter of which overlaps extensively with the traditional reading network’s frontal and temporal regions. Last, evidence of reduced FC between the cerebellum and cortical reading regions has been reported in individuals diagnosed with DD (Greeley et al, 2020). Reading fluency scores in the DD group positively correlated with FC between right cerebellar lobule VIII and the left AG.…”
Section: The Neural Bases Of Reading Fluencymentioning
confidence: 90%
“…Right crus I of the cerebellum interconnects with left hemisphere regions supporting reading and is activated in concert with these regions during reading tasks, as evident from a neuroimaging meta-analysis of typical adult readers (Martin et al, 2015). Functional and structural differences between readers with typical development and those diagnosed with DD have also been found in the posterolateral cerebellum (e.g., crus I, crus II, lobule VI; Greeley et al, 2020; Stoodley, 2014; Stoodley & Stein, 2011).…”
Section: The Reading Networkmentioning
confidence: 96%
See 1 more Smart Citation
“…There are few resting-state studies in typically developing children using alphabetic languages and some of these have used seed-to-voxel analysis focusing on regions known to be involved in reading and relating them to performance ( Koyama et al, 2011 , 2013 ; Cross et al, 2021 ). Of the few seed-to-voxel studies explicitly considering the cerebellum, Greeley and colleagues found a positive connection between right cerebellar lobule VIII and left angular gyrus to be related to reading scores in typical readers ( Greeley et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%